Understanding Transfer Pricing Behavior : The Influence of Tax Minimization, Bonuses, and Debt Covenants under Board Tenure Moderation - Azhaar Musyarofah; Badingatus Solikhah (Universitas Muhammadiyah Sorong, 2026)
This study examines the influence of debt covenants, tax minimization, and bonus mechanisms on transfer pricing, with board tenure as a moderating variable. A quantitative approach is applied using secondary data from non-financial companies listed on the Indonesia stock Exchange during 2020-2024. The sample is selected through purposive sampling and consists 3.723 firm-year observations. Data analysis uses descriptive statistics, panel regression and Moderated Regression Analysis (MRA), processed with Eviews. The findings show that tax minimization and bonus mechanisms have a positive and significant effect on transfer pricing, indicating that managers tend to use transfer pricing strategies when they are motivated to reduce taxes or when compensation structures encourage such practices. In contrast, debt covenants do not significantly affect transfer pricing, suggesting that creditor monitoring does not strongly restrict managerial decisions related to internal pricing policies. The result further reveal that board tenure does not moderate the effect of debt covenant, tax minimization, pr bonus mechanisms on transfer pricing. Overall, this study concludes that managerial incentives and compensation-driven motives play a bigger role in shaping transfer practices compared to monitoring mechanisms such as debt agreements or board tenure. These findings provide insights for regulators, investors, and companies on understanding the internal factors that drive transfer pricing behavior in Indonesia firms.